Log in to add a comment

Log in to add a comment

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

(x-y)² + (x+y)² = 0

x² + y² - 2xy + x² + y² + 2xy = 0

2(x² + y²) = 0

x² + y² = 0

y² = -x²

y = x sqrt(-1)

y = i x

x² + y² - 2xy + x² + y² + 2xy = 0

2(x² + y²) = 0

x² + y² = 0

y² = -x²

y = x sqrt(-1)

y = i x

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

(x-y)² + (x+y)² = 0

x² + y² - 2xy + x² + y² + 2xy = 0

2(x² + y²) = 0

x² + y² = 0

y² = -x²

as squrt can not be negative therfor no real value of y is possible but it can be imaginery

as negative roots only leds to imaginary parts

ans y=squart root -x^2

as -1=i^2 therfor y=ix

x² + y² - 2xy + x² + y² + 2xy = 0

2(x² + y²) = 0

x² + y² = 0

y² = -x²

as squrt can not be negative therfor no real value of y is possible but it can be imaginery

as negative roots only leds to imaginary parts

ans y=squart root -x^2

as -1=i^2 therfor y=ix